Effects of 2,4-dichlorophenoxyacetic acid (2,4-D), isolated and in a formulated product, on the functional parameters of isolated rat liver mitochondria - Polido, Lucas Roberto Ferreira; Miranda, C.A. [UNESP]; França, D.A [UNESP]; Mingatto, F.E. [UNESP]; Pereira, L.C. [UNESP] (Elsevier, 2024)
2,4-Dichlorophenoxyacetic acid (2,4-D) is a widely used herbicide with known implications for environmental and biological systems. Previous studies indicate its potential to interact with cellular structures, potentially impacting cellular energy and metabolism. This study aimed to investigate the toxicological effects of this molecule on isolated rat liver mitochondria, evaluating both isolated and formulated 2,4-D to comprehend the differential impacts on mitochondrial function. Our investigations did not reveal significant induction of oxidative stress, mitochondrial swelling or impacts on mitochondrial respiration; however, exposure to both forms of 2,4-D affected mitochondrial membrane integrity and function in a concentration-dependent manner, notably impacting mitochondrial ATP levels and membrane potential. Comparatively, the formulated product showed toxicity at lower concentrations regarding interaction with membranes and ATP levels (from 0.4 μM on) and isolated 2,4-D showed toxicity at lower concentrations regarding membrane potential dissipation (from 10 μM on). Notably, the effects on ATP levels and membrane fluidity suggest interactions within the mitochondrial lipid bilayer. The findings highlight that excipients in the commercial formulation of 2,4-D potentially alter its effects, underlining the importance of evaluating not only active ingredients but also formulations.